Effect of swimming training on stress-related metabolic parameters of diabetic and non-diabetic rats - Eduardo Campos; Aline Jarrete; Hygor Araujo; Suziane Cayres; José Campanholi Neto; Eliete Luciano (Revista Brasileira de Atividade Física e Saúde)
Physical training can be an useful strategy to attenuate the stress markers concentrations and hyperglycemia on type 1 diabetic rats. Thus, the purpose of the present study was to investigate the effects of swimming training on metabolic parameters and stress markers in diabetic and non-diabetic rats. Twenty-four adult male Wistar rats were recruited. The rats were randomly divided into four groups, sedentary control (SC), trained control (TC), sedentary diabetic (SD), and trained diabetic (TD). The diabetic rats received alloxan monohydrate and the trained rats swam for 60 minutes five times per week. The training load was 3.5% and 5% of body weight to diabetic and non-diabetic rats, respectively. After the euthanasia, blood samples for determination of corticosterone, insulin, and glucose levels were collected, and the adrenal weight, adrenal cholesterol concentration, gastrocnemius glycogen concentration, and muscle total protein content were also determined. To compare the groups, a variance analysis was used with Tukey´s post-hoc. The significance level of 5% was adopted. The adrenal weight was higher in SD (17.2±0.6g) than the other groups (SC: 12.2±0.8g; TC: 13.7±0.6g; TD: 14.3±0.8g), and TD had similar values of TC. The corticosterone level of SD was higher than SC and TC. The serum glucose was higher in the diabetic groups and insulin was lower in these groups. Six weeks of swimming training was efficient to reduce stress markers concentration in type 1 rats. Training may be a good tool to avoid the reduction on muscle protein content in type 1 diabetic rats.